2018
DOI: 10.1016/j.nbt.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ knowledge and opinions towards bollgard II® implementation in cotton production in western Burkina Faso

Abstract: In 2008, the commercial cultivation of Genetically Modified (GM) cotton (Bollgard II) started in Burkina Faso. The adoption rate increased rapidly in subsequent years to reach around 70% in 2014. Although some criticisms were raised concerning the suitability of the technology for the farming system in Burkina Faso, the introduction of transgenic cotton in the country was generally regarded as a great success. Despite this, during the 2016-2017 agricultural campaign, the government of Burkina Faso decided to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
15
1
Order By: Relevance
“…This smaller group of committed activists told me that they felt somewhat marginalized within their community. Further supporting this point, a survey conducted in 2015 of 324 farmers from 12 villages found that 88% of farmers disapproved of the state decision to suspend Bt cotton (Sanou et al, 2018). If anything, farmers target their ire more proximally at SOFITEX (Luna, 2019).…”
Section: Peasants Kicking Out Monsantomentioning
confidence: 97%
See 1 more Smart Citation
“…This smaller group of committed activists told me that they felt somewhat marginalized within their community. Further supporting this point, a survey conducted in 2015 of 324 farmers from 12 villages found that 88% of farmers disapproved of the state decision to suspend Bt cotton (Sanou et al, 2018). If anything, farmers target their ire more proximally at SOFITEX (Luna, 2019).…”
Section: Peasants Kicking Out Monsantomentioning
confidence: 97%
“…However, this message was factually inaccurate. Based on extensive interviews from 2016, the Burkinabè decision to not renew a contract with Monsanto was based entirely on Bt cotton's lower profitability for the cotton companies because of the shorter fibre length and less desirable ginning ratio (also see Bavier, 2017;Dowd-Uribe & Schnurr, 2016;Fok, 2016; L'Economiste du Faso, 2016;Sanou, Gheysen, Koulibaly, Roelofs, & Speelman, 2018).…”
Section: Peasants Kicking Out Monsantomentioning
confidence: 99%
“…However, a third level of four insecticide treatments was defined to see whether there is a tradeoff with other characteristics. This third level is also sustained by the trends in Bt cotton farms, where an increased abundance of non-targeted insects was observed, so that the number of required insecticide treatment tends to increase [23].…”
Section: Identification Of Attributes and Levelsmentioning
confidence: 93%
“…This level of appreciation from small-scale farmers could be related to the findings of Renaudin et al [18], who highlighted the financial risks for small farmers attributed to Bt cotton cultivation owing to the high seed price of Bt cotton. More recently, Sanou et al [23] also found that the seed price policy was the main constraint listed by small-scale farmers. When considering the ASC for the large farmers groups, our model seems to suggest that they were satisfied with their current situation regardless of whether they were growing the Bt or non-Bt variety.…”
Section: Conditional Logitmentioning
confidence: 98%
See 1 more Smart Citation